2018
DOI: 10.5958/2348-1773.2018.00001.2
|View full text |Cite
|
Sign up to set email alerts
|

Authorship pattern of open access social science journals published in India

Abstract: The purpose of the study is to identify the pattern of authorship and the collaboration of six Indian Open Access Social Science Journals during 2011-2015. Bibliographic data were collected from 785 articles based on authorship studies such as authorship pattern, number of authors, Indian versus foreign authors and citation rate. The study found that Collaborative Coefficient and Degree of Collaboration of these articles were 0.39 and 0.62 respectively, which clearly indicate that the research trend is towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Tables 4 describe the distribution of cited and uncited status of the articles which have retrieve from Google Scholar. Among the papers it has been observed that overall 62.33% articles have cited, which have a similarity with previous studies (Kirtania, 2018;Kirtania & Chakrabarti, 2018). Based on the citation trend it has been observed that out of fifteen journals ten journals have more than 50% cited papers which reveals the quality of Indian social science journals.…”
Section: Methodssupporting
confidence: 81%
“…Tables 4 describe the distribution of cited and uncited status of the articles which have retrieve from Google Scholar. Among the papers it has been observed that overall 62.33% articles have cited, which have a similarity with previous studies (Kirtania, 2018;Kirtania & Chakrabarti, 2018). Based on the citation trend it has been observed that out of fifteen journals ten journals have more than 50% cited papers which reveals the quality of Indian social science journals.…”
Section: Methodssupporting
confidence: 81%
“…A subfield of scientiometric called "authorship study" looks into the various aspects of authorship, including the type of authors, the type and level of collaboration, the influence of citations, and the trend of authorship collaboration. This trend is concerned with analysing the traits and patterns of authorship in academic works 9 . Analysing author productivity, influence, connections, partnerships, and affiliations with other authors is part of this 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, most of the research has been conducted jointly for the overall growth of information communication technology worldwide (Patra, Bhattacharya & Verma, 2006;Kirtania, 2021). This collaboration pattern may have one to multiple authors, and may involve domestic or international researchers from any organization in the country, starting with colleagues from the same organization (Kirtania & Chakrabarti, 2018). In recent times, there has been a lot of work on authorship patterns, but the current status of existing publications on authorship pattern, growth, times cited, core publication source should be analyzed.…”
Section: Introductionmentioning
confidence: 99%